Fluorescent Nanosensor for Probing Histone Acetyltransferase Activity Based on Acetylation Protection and Magnetic Graphitic Nanocapsules. Issue 7 (2nd October 2014) - Han, Yitao; Li, Pei; Xu, Yiting; Li, Hao; Song, Zhiling; Nie, Zhou; Chen, Zhuo; Yao, Shouzhuo
<x xml:space="preserve">Abstract</x> Protein acetylation catalyzed by histone acetyltransferases (HATs) is significant in biochemistry and pharmacology because of its crucial role in epigenetic gene regulations. Herein, an antibody‐free fluorescent nanosensor is developed for the facile detection of HAT activity based on acetylation protection against exopeptidase cleavage and super‐quenching ability of nanomaterials. It is shown for the first time that HAT‐catalyzed acetylation could protect the peptide against exopeptidase digestion. FITC‐tagged acetylated peptide causes the formation of a nano‐quenchers/peptide nano‐complex resulting in fluorescence quenching, while the unacetylated peptide is fully degraded by exopeptidase to release the fluorophore and restore fluorescence. Four kinds of nano‐quenchers, including core–shell magnetic graphitic nanocapsules (MGN), graphene oxide (GO), single‐walled carbon nanotubes (SWCNTs), and gold nanoparticles (AuNPs), are comprehensively compared. MGN shows the best selectivity to recognize the acetylated peptide and the lowest detection limit because of its excellent quenching efficiency and magnetic enrichment property. With this MGN‐based nanosensor, HAT p300 is detected down to 0.1 nM with wide linear range from 0.5 to 100 nM. This sensor is feasible to assess HAT inhibition and detect p300 activity in cell lysate. The proposed nanosensor is simple, sensitive, and cost‐effective for HAT assay, presenting a promising toolkit for epigenetic research and HAT‐targeted drug discovery.